2005
DOI: 10.1111/j.1460-9592.2005.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bacteremia following nasotracheal intubation

Abstract: Since the occurrence of bacteremia after nasotracheal intubation is hazardous for patients at risk for developing infective endocarditis, to prevent further complications prophylactic antibiotic treatment is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the incidence was higher when electric sonicating toothbrushes rather than conventional tooth brushes were used (12). The latter finding on bacteremia under general anesthesia needs to be interpreted cautiously, as prolonged intubation in itself causes bacteremia and the magnitude of bacteremia in terms of incidence and diversity increases with the duration of the intubation (93).…”
Section: Personal Oral Hygiene Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the incidence was higher when electric sonicating toothbrushes rather than conventional tooth brushes were used (12). The latter finding on bacteremia under general anesthesia needs to be interpreted cautiously, as prolonged intubation in itself causes bacteremia and the magnitude of bacteremia in terms of incidence and diversity increases with the duration of the intubation (93).…”
Section: Personal Oral Hygiene Measuresmentioning
confidence: 99%
“…When surgical incisions were made to facilitate the extraction of teeth, particularly impacted third molars, with subsequent insertion of sutures, nearly 10% of individuals had a bacteremia following the removal of sutures, and the incidence was not reduced by the use of preoperative antiseptic rinses (16). Despite the fact that intubation is associated with bacteremia (93), no significant change in bacteremic incidence was observed when extractions were performed under general anesthesia (128). In addition, there is no apparent change in the incidence of bacteremia with increased numbers of teeth extracted or the use of mucoperiosteal elevators (103,111,133).…”
Section: Tooth Extractionmentioning
confidence: 99%
“…On the other hand, bleeding from instrumentation of the upper airway via tracheal intubation has been shown to be associated with bacteremia. 20 , 21 Several authors 22-29 reported that bacteremia occurs more frequently after nasotracheal than orotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Onçag et al. [16] stated that the difference in the incidence of bacteraemia after nasotracheal and orotracheal intubation is related not to the procedure but rather to the anatomical pathway and the resident flora. In contrast to these reports, the incidence of post‐intubation bacteraemia in the present series was not affected by the route of intubation.…”
Section: Discussionmentioning
confidence: 99%